2017
DOI: 10.4103/ijd.ijd_115_17
|View full text |Cite
|
Sign up to set email alerts
|

Use of fine needle aspirate from peripheral nerves of pure-neural leprosy for cytology and polymerase chain reaction to confirm the diagnosis: A follow-up study of 4 years

Abstract: Background:Pure neural leprosy (PNL) still remains a diagnostic challenge because of the absence of sine qua non skin lesions of leprosy and a confirmatory diagnostic method. The authors had earlier described a simple yet objective technique of combining fine needle aspiration cytology (FNAC) coupled with a multiplex polymerase chain reaction (PCR) in a pilot study, wherein the technique showed promise of a reliable diagnostic tool. In the pursuit of further evidence, the authors carried out a 4-year study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…In patients with pure neuritic leprosy (no skin lesions and negative slit skin smear bacilloscopy), it is important to perform qPCR for M. leprae DNA on slit skin smears and/or skin biopsies as this increases the sensitivity for diagnosing leprosy 50,53 . Fine needle aspiration cytology of the nerve can also demonstrate the lepra bacilli and epithelioid granulomas and has been shown to have comparable yields to nerve biopsy, while being less invasive 54 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with pure neuritic leprosy (no skin lesions and negative slit skin smear bacilloscopy), it is important to perform qPCR for M. leprae DNA on slit skin smears and/or skin biopsies as this increases the sensitivity for diagnosing leprosy 50,53 . Fine needle aspiration cytology of the nerve can also demonstrate the lepra bacilli and epithelioid granulomas and has been shown to have comparable yields to nerve biopsy, while being less invasive 54 …”
Section: Methodsmentioning
confidence: 99%
“…50,53 Fine needle aspiration cytology of the nerve can also demonstrate the lepra bacilli and epithelioid granulomas and has been shown to have comparable yields to nerve biopsy, while being less invasive. 54 2.6 | Indications for nerve biopsy (moderate importance)…”
Section: Pure Neuritic Leprosymentioning
confidence: 99%
“…Earlier, some of the authors have shown similar presentations of leprosy and with similar proven technologies. [ 4 5 6 ] Though he was given a repeated dose of steroids for a short duration, with which tender nodules subsided, tenosynovitis kept on progressing. The patient was given combination therapy of thalidomide 200 mg per day plus prednisone 50 mg per day and MDT was restarted.…”
Section: Casementioning
confidence: 99%
“…Pure neural leprosy can be diagnosed by nerve biopsy taken from a small cutaneous or subcutaneous nerve . From a larger nerve, a fine‐needle aspiration can be done for cytology and bacteriology with PCR . A problem is that even within one biopsy, the histopathology of one site may differ from the other.…”
Section: Diagnosismentioning
confidence: 99%